The global financial crisis impact on stock market efficiency: a Fourier unit root tests analysis - Muneer Shaik; Pratik Kamdar; Nishad Nawaz; Mustafa Raza Rabbani; Sahar E-Vahdati; Mohd. Afzal Saifi; Himani Grewal (Cogent Economics & Finance, 2024)
This study investigates how the Global Financial Crisis has affected the weak-form Efficient Market Hypothesis (EMH) on the stock prices of sixteen nations throughout the globe based on a suite of Fourier unit root tests. Considering the smooth structural breaks, we employed the Fourier-based unit root tests to assess the weak-form efficient market hypothesis. We used multiple frequency datasets of global financial stock market indexes that span over 20 years to have comprehensive analysis and robustness in the results. The study is performed from distinct sub-sample periods of the global financial crisis, including the pre-crisis period (2000-2007), the crisis and post-crisis period (2008-2020), and the overall sample period (2000-2020). We observed seven stock markets in the total sample period and twelve in the pre-crisis period, which were weak-form efficient across different frequency data sets. During the crisis and post-crisis period, just four out of sixteen stock market indexes were found to be weak in efficiency based on Fourier unit root tests. Given the superior properties of the Fourier unit root tests, this study reiterates that investors may receive a stream of arbitrage benefits in all markets due to the inefficiency of these countries. We offer investment implications that enable forecasting future stock price changes based on past performance and creating trading methods that produce anomalous profits.
Keywords: C12; C58; G12; G14; 330; Global financial crisis; stockprices; Fourier unit roottest; efficient market hypothesis